Hemophagocytic syndrome triggered by intense physical activity and viral infection in a young adult female with three heterozygous mutations in Munc-18-2 - Marković Olivera; Janić Dragana; Pavlović Milorad; Tukić Ljiljana; Janković Srđa; Filipović Branka; Marisavljević Dragomir (Vojnosanitetski Pregled)
Introduction. Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially life-threatening, hyperinflammatory syndrome caused by severe hypercytokinemia due to a highly stimulated, but ineffective immune response. Case report. We reported a 19-year-old woman presenting with fever, muscle and joint pain and sore throat. After diagnostic procedures we made the diagnosis of hemophagocytic lymphohistiocytosis (7 of 8 HLH-2004 diagnostic criteria) caused by Ebstein-Barr viral infection and trigerred by the intense physical activity. Genetic analysis showed three different sequence changes in Munc-18-2, two splice acceptor side mutations/changes affecting exon 10 (c.795–4 C > T) and exon 15 (c.1247–10 C > T) and a missense mutation c.1375 C > T; p.Arg 459 Trp. All mutations were in heterozygous state and their significance in pathogensis of HLH is not clear. After treatment with corticosteroids and cyclosporin A complete clinical remission was achieved. Conclusion. The presented case history suggests the possibility that mutations of undetermined clinical significance in a gene associated with primary HLH may underlie some cases of secondary HLH, probably by causing a partial, rather than total or subtotal, impairment of encoded protein function. Our case also suggests that strenuous physical activity (in apparent synergy with viral infection) can trigger HLH.